Techno-economics analysis of biodiesel production from palm, jatropha curcas and calophyllum inophyllum as biofuel - T.M.I. Mahlia; H.C. Ong; H.H. Masjuki (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Transportation sector has a dominant role in global fuel consumption andgreenhouse gas emissions consequently. Biodiesel is a renewable energy that has great potential to serve as an alternative fuel to fossil diesel in diesel engine. Besides the technical barriers, there are several nontechnical limiting factors, which impede the development of biodiesel. Therefore, this study is focused on biodiesel production and techno-economic comparison among palm, jatropha curcas and calophyllum inophyllum biodiesel as transportation fuel. Moreover, the present study attempts to find out the impact of biodiesel implementation towards the energy scenario, environmental and economy. The largest economic factor for biodiesel production is feedstock cost. Furthermore, replacing 5% of diesel fuel with biodiesel fuel in road transport can reduce theCO2 emission up to 1200 ktons in year 2031. When the subsidy policy and tax exemption are implemented, biodiesel fuel is more competitive than fossil diesel at the current production costs. Therefore, this study serves as a guideline for further investigation on biodiesel production and other limitation factors before the wider utilization of biodiesel can be implemented.